THE PAN-AFRICAN CULTURAL FESTIVAL - TWO VIEWS (International Library of African Music, 1970)
We Africans are a people who like to wrestle and it is time for politician, artist and critic to tie their wrappers firmly and prepare for the bout. The organizers of the festival succeeded in bringing together these three traditional enemies, all whetting their palms in eager anticipation of the match. But it never took place. Instead, official delegation after official delegation spent their time trying to convince fellow Africans that their particular country has a culture or that many centuries ago a national literature was in fact started. The time devoted to government policy statements on culture made the festival sound like a meeting of the O.A.U., this time with a very restless audience of artists.
Keywords: African Music